What is Rule by Law? - Balasubramaniam, Ratna Rueban (Journal of Malaysian and Comparative Law, 2018)
My aim in this paper is to sharpen the popularly perceived association between rule by law and worries about arbitrary power. I argue that the use of law as a cloak for arbitrary power or rule by law is pathological to the rule of law because it undermines law’s capacity to facilitate or guide conduct. My analysis of rule by law pivots on the argument that the rule of law is an ideal of workable legal order understood as a framework of norms for facilitating the interests of legal subjects. The rule of law is therefore a moral idea to the extent that the attempt to construct and maintain such an order requires engaging the legal subject, as a rational moral agent possessed of vital interests. Since rule by law involves the attempt to use the law in a way that does not involve the systematic engagement of the legal subject so conceived but which nevertheless tries to project rule-of-law legitimacy by trading on the rule of law, rule by law strains the rule of law and corrupts the workability of legal order as a framework for facilitating the salient moral interests of legal subjects thus by damaging the rational and moral foundations of legal order. It is therefore apt to conceive of rule by law as a form of juridical pathology.